(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Arnold B. Udoka Abstract— This paper puts Ruth Finnegan’s 1970 universal claim that “drama does not exist in Africa” (Finnegan, 1970, p. 508) on trial. Finnegan did not write on Anaañ drama at any time and never cited John Cowan Messenger’s Anaañ ethnography. In this discourse, she encounters Messenger’s evidence for the first time in the academic court. Read through Edward Said’s Orientalism (1978) and Gayatri Spivak’s epistemic violence (1988), her universal delegitimisation is exposed as discourse produced through selective ignorance, not data. Her Eurocentric criteria constructed African cultures, including Anaañ, as absence by measuring performance against European proscenium theatre, despite Messenger’s 1959 documentation of Ekoñ [Messenger’s “Ekong”] and Affioñ [Messenger’s “Affiong/Offiong”] among the Anaañ/Oron. Messenger recorded Ekoñ with staged conflict, role-played characters, plot, arena staging, audience judgment, and social control. He also recorded Affioñ, teenage courtship drama enacted through dance with plot, character, and conflict. In Anaañ language, the people are Anaañ and the drama is Affioñ, meaning “the moon.” Messenger maintained colonial naming and orthography for academic consistency in 1962 and 1971 publications. This paper introduces Messenger’s Anaañ evidence into the discourse for the first time to refute Finnegan’s universal claim that “drama does not exist in Africa” (Finnegan, 1970, p. 508). African scholarship delivers the counter-verdict: Ogunbiyi (1981) asserted “Ibibio [Anaañ] drama [Ekoñ and Affioñ] surpasses... modern European drama” (p. 23). Contemporary Ekoñ and Affioñ performance confirms Messenger. The implication is methodological: African theatre studies must reject universal claims about “Africa” and center specific ethnographies like Anaañ Ekoñ and Affioñ. The subaltern speaks in Anaañ by its right name.